Carbon monoxide poisoning - cases, pathophysiology, management - Kubicka, Magdalena; Dębiec, Paweł; Wilk, Joanna; Szydłowski, Przemysław; Makarewicz, Magdalena; Porzak, Mikołaj; Szyłkajtis, Natalia (Journal of Education, Health and Sport, 2023)
Carbon monoxide poisoning is a common clinical problem, especially in autumn and winter. Carbon monoxide is an odorless, colorless gas and poisoning causes hypoxia, cell damage and consequently, can lead to death. Carbon monoxide exposure is measured directly from blood samples and expressed as a percentage of carboxyhemoglobin or indirectly using carbon monoxide in the breath. Carboxyhemoglobin percentage is the most commonly used biomarker of carbon monoxide exposure. Although the diagnosis of carbon monoxide poisoning can be confirmed by the detection of elevated levels of carboxyhemoglobin in the blood, the presence of clinical signs after known exposure to carbon monoxide should not be ignored. Carbon monoxide poisoning can have lasting effects. Physicians evaluating patients with acute poisoning should initiate treatment with normobaric oxygen and consider treatment with hyperbaric oxygen. Often, complete recovery after poisoning may not be possible and you should then refer for the treatment of complications to appropriate specialists.